Association of Family History of Cancer with Clinical and Pathological Outcomes for Prostate Cancer Patients on Active Surveillance. Issue 2 (4th August 2022) - Jibara, Ghalib A.; Perera, Marlon; Vertosick, Emily A.; Sjoberg, Daniel D.; Vickers, Andrew; Scardino, Peter T.; Eastham, James A.; Laudone, Vincent P.; Touijer, Karim; Lin, Xin; Carlo, Maria I.; Ehdaie, Behfar
Abstract : Purpose: The impact of germline mutations associated with hereditary cancer syndromes in patients on active surveillance (AS) for prostate cancer is poorly defined. We examined the association between family history of prostate cancer (FHP) or family history of cancer (FHC) and risk of progression or adverse pathology at radical prostatectomy (RP) in patients on AS. Materials and Methods: Patients on AS at a single tertiary-care center between 2000–2019 were categorized by family history. Disease progression was defined as an increase in Gleason grade on biopsy. Adverse pathology was defined as upgrading/upstaging at RP. Multivariable Cox and logistic regression models were used to assess association between family history and time to progression or adverse pathology, respectively. Results: Among 3, 211 evaluable patients, 669 (21%) had FHP, 34 (1%) had FHC and 95 (3%) had both; 753 progressed on AS and 481 underwent RP. FHP was associated with increased risk of progression (HR 1.31; 95% CI, 1.11–1.55; p=0.002) but FHC (HR 0.67; 95% CI, 0.30–1.50; p=0.3) or family history of both (HR 1.22; 95% CI, 0.81–1.85; p=0.3) were not. FHP, FHC or both were not associated with adverse pathology at RP (p >0.4). Conclusions: While FHP was associated with an increased risk of progression on AS, wide confidence intervals render this outcome of unclear clinical significance. FHC was not associated with risk of progression on AS. In the absence of known genetically defined hereditary cancer syndrome, we suggest FHP and/or FHC should not be used as a sole trigger to preclude patients from enrolling on AS.